Optimizing the Role of Village-Owned Enterprises (BUMDes) in the Management of Village Funds in Gelonggong Village, Brebes Regency - Maulana, Bella Arief; Sutjiatmi, Sri; Habibullah, Akhmad (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the optimization of the role of Village-Owned Enterprises (BUMDes) in the management of Village Funds in Gelonggong Village, Brebes Regency. The research focuses on assessing the effectiveness of BUMDes in improving village financial governance, transparency, accountability, and its contribution to community economic development. The study employs a quantitative approach through the distribution of questionnaires to 75 respondents, consisting of BUMDes administrators, village officials, and community service users. Data analysis was carried out using descriptive statistics and simple linear regression tests. The findings indicate that the role of BUMDes is categorized as moderately optimal, with an average score of 3.72 (on a 1–5 scale), and has a significant influence on Village Fund management. Its effective contribution accounts for 31.2% of the improvement in Village Fund governance. The study concludes that BUMDes Gelonggong has played a strategic role; however, further enhancements are needed in human resource capacity, business innovation, and the digitalization of financial reporting.